STUDI KASUS KECANDUAN GAME ONLINE PESERTA DIDIK KELAS XI SMA NEGERI 1 SUNGAI RAYA - Suri, Maria Hesty; Asrori, Muhammad; Wicaksono, Luhur (Universitas Tanjungpura, 2022)
This research aims identifying and alleviate the case of students who are addicted to playing online games at the State High School 1 Sungai Raya. The approach used is a qualitative approach with a descriptive method and a case study research form. The case subjects in this study were two people with the initials UDS and RM. Data collection techniques in this study used were interviews, home visits, and documentation studies. The results of the treatment for Subject Case I, namely: a) study participants have been able to sincerely accept what has happened, b) study participants are more mature in responding to problems received, c) study participants limit playing online games by making a time schedule and reducing time playing online games into a maximum of 2 hours only that was previously 5-6 hours, d) there is an awareness of wanting to make changes, e) study participants have willingness to socialize, and f) study participants want to develop their potential. The results of the treatment of Case II Subjects are as follows: a) study participants want to develop their study awareness, b) study participants limit the online games playing, c) study participants are able to manage their behaviors, d) research participants are able to socialize with friends, and d) one of research participants is able to forgive his family's death and is always grateful for the situation.